2000
DOI: 10.1088/0953-8984/13/3/311
|View full text |Cite
|
Sign up to set email alerts
|

Integral evaluation in the mathematical and numerical modelling of high-electron-mobility transistors

Abstract: The main processes involved in the mathematical and numerical modelling of high-electron-mobility transistors are presented. The governing equations must be solved rapidly and accurately for the simulation to be of use in CAD (computer-aided design) packages. New analytic approximations are derived for certain integrals which arise in the simulation, enabling these integrals to be calculated rapidly. Results produced in this way are compared with those produced using earlier less accurate approximations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…o odinger wave equation. The electron density and electron energy densities were approximated with fully degenerate statistics [13]. A novel model for Ohmic contacts was used for the source and drain boundary conditions, which improved the representation of the device and enhanced simulation stability.…”
Section: Resultsmentioning
confidence: 99%
“…o odinger wave equation. The electron density and electron energy densities were approximated with fully degenerate statistics [13]. A novel model for Ohmic contacts was used for the source and drain boundary conditions, which improved the representation of the device and enhanced simulation stability.…”
Section: Resultsmentioning
confidence: 99%
“…The final column labelled 'previous' gives the corresponding results obtained in the first attempt which used a non-GA method [1]. The results of this table show that the relative percentage Figure 3.…”
Section: Comparison Of the Performances Of The Three Statisticsmentioning
confidence: 99%
“…The associated Fermi integrals which arise in the modelling of HEMTs are defined by [1] I r ða; bÞ 1 Gðr þ 1Þ In order to discuss the nature and use of these integrals, consider the four-layer HEMT device whose two-dimensional cross-section is shown in Figure 1. It consists of layers of different semiconducting materials, in this case of GaAs and AlGaAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the aim of the present, the corrected accurate analytical method established in Ref. [11] has been applied to realistic the GaN based multilayer device to optimize their design. Therefore it is going to be shown that the instant mathematical and numerical modeling engages an important role in picturing the corresponding energy and electron densities for such structures.…”
Section: Introductionmentioning
confidence: 99%